Carrier-wave Rabi flopping signatures in high-order harmonic generation. (August 2015) - Ciappina, M F; Pérez-Hernández, J A; Landsman, A S; Zimmermann, T; Lewenstein, M; Roso, L; Krausz, F
Synopsis: We present theoretical investigations of carrier-wave Rabi flopping (CWRF) in real atoms by studying high-order harmonic generation in alkali species. We concentrate on the features of the third harmonic of Na and K atoms. For pulse areas of 2 π and Na atoms, a characteristic unique peak appears, which, after analyzing the ground state population, we correlate it with the conventional Rabi flopping. On the other hand, for larger pulse areas and K atoms, CWRF occurs, and it is associated with a more complex structure in the third harmonic. These new characteristics indicate the breakdown of the area theorem, as was already demonstrated in narrow band gap semiconductors.